If 3 x + 2 x 1 = 3 , what is the value of 8 x 3 + 2 7 x 3 1 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution. I solve it using Jake pham's method.
Or you can take variables is also (27x³,8x³)
sir ki trick se kr
3 x + 2 x 1 = 3 = > 2 x + 3 x 1 = 2 Cube the equation: 8 x 3 + 2 7 x 3 1 + 3 x 2 x x 3 x 1 x ( 2 x + 3 x 1 ) = 8 => 8 x 3 + 2 7 x 3 1 = 8 -4 = 4
how did you get that 2x+1/3x = 2 ?!
he multiply by 3/2
3x + 2 x 1 =3 , multiply both sides by 2x and then divide by 3x to obtain 2x+ 3 x 1 =2
now take cube on both sides
using formula : ( a + b ) 3 = a 3 + b 3 + 3 a b ( a + b )
=> ( 2 x ) 3 + ( 3 x 1 ) 3 + 3 ( 2 x ) ( 3 x 1 )[ 2 x + 3 x 1 ]= 2 3
(bcoz 2 x + 3 x 1 =2
( 2 x ) 3 + ( 3 x 1 ) 3 + 3 ( 2 x ) ( 3 x 1 )[2]= 2 3
now after cancelling the same terms we have
( 2 x ) 3 + ( 3 x 1 ) 3 +2[2]= 2 3
8 x 3 + 2 7 x 3 1 +4=8
=> 8 x 3 + 2 7 x 3 1 =8-4 => 4 ANS....
I understood your solution the most thank you so much. O-o
Multiply the given equation with 3 2 and cube the obtained expression and simplify further to obtain the result as 4
Can you explain in further detail so that others can easily understand what you wrote?
8 x 3 + 2 7 x 3 1
= ( 2 x + 3 x 1 ) ( 4 x 2 − 3 x 2 x + 9 x 2 1 )
= ( 2 x + 3 x 1 ) ( 4 x 2 − 3 2 + 9 x 2 1 )
We know that a 2 − a b + b 2 = ( a + b ) 2 − 3 a b , hence the expression above is:
= ( 2 x + 3 x 1 ) ( ( 2 x + 3 x 1 ) 2 − 3 ( 3 2 ) ) = ( 2 x + 3 x 1 ) [ ( 2 x + 3 x 1 ) 2 − 2 ]
We need to find ( 2 x + 3 x 1 ) :
From the 1st equation that was given ( 3 x + 2 x 1 = 3 )
3 2 × ( 3 x + 2 x 1 ) = 3 × 3 2
2 x + 3 x 1 = 2
Therefore:
8 x 3 + 2 7 x 3 1 = ( 2 x + 3 x 1 ) [ ( 2 x + 3 x 1 ) 2 − 2 ] = ( 2 ) ( 2 2 − 2 ) = 4
Here my way frnds first we rearrange the term that is given in the question I.e 3x +1/2x =3 3(x-1)= -1/2x 2(x-1)=-1/3x 2x +1/3x = 2 8x^3+ 1/27x^3 in to factorize by using a^3 + b ^3 formula nd plug the value obtain from above to find the answer .
We have that 3 x + 2 x 1 = 3 ⟹ 2 x = 3 x 6 x − 1 And we need to evaluate E = 8 x 3 + 2 7 x 3 1 = ( 2 x + 3 x 1 ) ( ( 2 x + 3 x 1 ) 2 − 2 3 x 2 x − 3 x 2 x ) ⋯ ( 1 ) Now plugging 2 x = 3 x 6 x − 1 in the 1st equation we get E = ( 3 x 6 x − 1 + 3 x 1 ) ( ( 3 x 6 x − 1 + 3 x 1 ) 2 − 3 4 − 3 2 ) E = 2 ( 2 2 − 2 ) = 4
This question just requires noticing that 2 x + 3 x 1 = 3 2 ( 3 x + 2 x 1 )
Thus, we get that 2 x + 3 x 1 = 3 2 . 3 = 2
And then we use the fact that
8 x 3 + 2 7 x 3 1 = ( 2 x + 3 x 1 ) 3 − 3 ( 2 x ) ( 3 x 1 ) ( 2 x + 3 x 1 ) = ( 2 x + 3 x 1 ) 3 − 2 ( 2 x + 3 x 1 )
And thus we get
8 x 3 + 2 7 x 3 1 = 2 3 − 2 ( 2 ) = 8 − 4 = 4
Problem Loading...
Note Loading...
Set Loading...
⇒ 3 x + 2 x 1 = 3
Cubing both sides.
( 3 x ) 3 + ( 2 x 1 ) 3 + 3 × 3 x × 2 x 1 ( 3 x + 2 x 1 ) = 2 7
2 7 x 3 + 8 x 3 1 + 2 2 7 = 2 7
2 7 x 3 + 8 x 3 1 = 2 2 7
Multiplying 2 7 8 both sides.
( 2 7 x 3 × 2 7 8 ) + ( 8 x 3 1 × 2 7 8 ) = 2 2 7 × 2 7 8
⇒ 8 x 3 + 2 7 x 3 1 = 4